Postoperative Troponin Measurement as a Screening Tool for Adverse Cardiac Events in Adult Patients Undergoing Moderate Or Major Non-Cardiac Surgery. Issue 6 (November 2017) - Coric, D.; Smith, N. A.
Elevated troponin levels within three days of surgery are strongly linked to major adverse cardiac events (MACE). However the value of screening with troponin measurements is controversial. The extent to which this is done in routine practice is uncertain. We examined the medical records of all patients ≥45 years of age undergoing moderate or major non-cardiac surgery in our tertiary referral hospital over a six-month period. We determined how many patients had a troponin (TnT) measurement recorded in the first three days postoperatively, how many of these were abnormal, and the occurrence of MACE within 30 days. Two thousand and two hundred patients underwent 2, 577 operations that met the study criteria. A postoperative TnT was measured after 4.5% of operations. Thirty-eight percent of patients with a recorded TnT measurement, and 44% of those with an abnormal measurement, experienced a MACE within 30 days. The sensitivity of an abnormal TnT to detect MACE was 86%. The specificity was low at 32% with a false positive rate of 56%. Patients with an abnormal TnT result had an increased risk of MACE (23%). The 'number needed to measure' to detect one patient with MACE was 4.4. In our institution, postoperative TnT levels were rarely measured and were used as a diagnostic rather than as a screening tool. The high false positive rate for MACE prediction limits its potential value as a screening tool. The test could be considered useful if it leads to further investigation, and may be best considered as one component of a multivariate approach to cardiac risk evaluation and diagnosis.